Mengklarifikasi Istilah“Jumat Agung”Menurut Kajian Tipologi Berdasarkan Keluaran 12:1-42 - Yohanis Banamtuan (Sekolah Tinggi Teologi Internasional Harvest Tangerang, 2022)
Easter is a very sacred holiday for Christians, but as time goes on there are other terms attached to this sacred holiday and not all of these terms give meaning to Easter, on the contrary, it has the potential to obscure its meaning. One of the terms referred to above is the term “Good Friday.” This term has been used for a long time and without realizing it has reduced and confused the true meaning of Easter so that Easter is only understood as an event of Christ's resurrection, while the event of Jesus' death is commemorated as